An analysis of qualitative responses from a UK survey of the psychosocial wellbeing of people with skin conditions and their experiences of accessing psychological support. (19th August 2021) - Wheeler, M.; Guterres, S.; Bewley, A. P.; Thompson, A. R.
Summary: Background: Skin conditions have a large emotional, psychological and psychiatric impact on the individual. The All‐Party Parliamentary Group on Skin (APPGS) commissioned a qualitative survey to further explore this relationship alongside the experiences of those accessing services in relation to these difficulties in the UK. Aim: To examine the experiences of UK individuals living with a skin condition, and their views of seeking and receiving psychological treatment. This survey formed part of the evidence collected in the preparation of the APPGS Mental Health and Skin Disease report. Methods: A free‐text electronic survey was widely distributed by professional bodies and skin‐related charities. Responses were analysed using descriptive thematic analysis and descriptive statistics. Data for each question were classified and labelled, leading to the development of a coding frame. Inter‐rater reliability was assessed using Cohen kappa statistic. Results: In total, 544 participants (84% female) completed the survey. The majority of respondents had inflammatory skin diseases such as eczema (43%) or psoriasis (33%). The thematic analysis revealed five key themes associated with impact on mood; impact of intimacy; impact on activities of daily living; lack of recognition from others of the impact; and lack of accessible services. Conclusion: The survey demonstrates that there is an urgent need to improve both awareness of the impact that skin conditions can have, and for the provision of psychological services to address this impact.